Literature Study of Tourism Village Development Regulation Based on Local Wisdom Aspects of The Community in Kelong Village, Bintan Coast District, Indonesia - Lapotulo, Nensi; Afriani, Miratia; Kawakibi Pristiwasa, I Wayan Thariqy (Cita Konsultindo Research Center, 2024)
Tourism is a phenomenon that arises due to the interaction between tourists, service providers/tourism industry, and the government in providing facilities and services that support tourism activities. These various interactions form a system that is interconnected with each other. The tourism system is described as closed, but this model can be used to analyze the crucial components of providing attractiveness to a tourist destination. Kelong Village, with its unique combination of red soil, green sea, and blue sky, presents a special dish that stuns with Kelong Island's beauty. The journey to this charming location involves breaking through a pine forest flanked by lakes and beaches, a challenge heightened by the high humidity. The island's unspoiled mangroves, which grow on the beach, offer a unique fishing experience. The charm of the sunset is also a beauty that tourists can enjoy. It is important to note that the beauty of Kelong Village is not just in its natural attractions but also in the local wisdom that underpins its community-based tourism. This local wisdom is a cultural aspect we should all appreciate and respect, enriching our understanding of the world and the communities we visit. Our study is based on a comprehensive normative juridical research method, a robust and widely respected approach in the field. This method, known for its reliability and accuracy, has produced insightful results, instilling a high level of confidence in the credibility of our study. You can trust the information presented in this study, knowing that it is based on a solid and reliable research method. We have taken every measure to ensure the accuracy and reliability of our findings so you can be confident in the information we present.